Extrinsic Green Photoluminescence from the Edges of 2D Cesium Lead Halides. Issue 33 (24th June 2019) - Wang, Chong; Wang, Yanan; Su, Xinghua; Hadjiev, Viktor G.; Dai, Shenyu; Qin, Zhaojun; Calderon Benavides, Hector A.; Ni, Yizhou; Li, Qiang; Jian, Jie; Alam, Md. Kamrul; Wang, Haiyan; et al.
Abstract: Since the first report of the green emission of 2D all‐inorganic CsPb2 Br5, its bandgap and photoluminescence (PL) origin have generated intense debate and remained controversial. After the discovery that PL centers occupy only specific morphological structures in CsPb2 Br5, a two‐step highly sensitive and noninvasive optical technique is employed to resolve the controversy. Same‐spot Raman‐PL as a static property–structure probe reveals that CsPbBr3 nanocrystals are contributing to the green emission of CsPb2 Br5 ; pressure‐dependent Raman‐PL with a diamond anvil cell as a dynamic probe further rules out point defects such as Br vacancies as an alternative mechanism. Optical absorption under hydrostatic pressure shows that the bandgap of CsPb2 Br5 is 0.3–0.4 eV higher than previously reported values and remains nearly constant with pressure up to 2 GPa in good agreement with full‐fledged density functional theory (DFT) calculations. Using ion exchange of Br with Cl and I, it is further proved that CsPbBr3− x X x (X = Cl or I) is responsible for the strong visible PL in CsPb2 Br5− x X x . This experimental approach is applicable to all PL‐active materials to distinguish intrinsic defects from extrinsic nanocrystals, and the findings pave the way for new design and development of highly efficient optoelectronic devices based on all‐inorganic lead halides. Abstract : Same‐spot Raman photoluminescence with two lasers in a diamond anvil cell under hydrostatic pressure reveals that CsPbBr3 nanocrystals, mostly located on the edges of CsPb2 Br5 2D platelets, are responsible for CsPb2 Br5 's green emission. This sensitive noninvasive technique combining static and dynamic probes establishes a one‐to‐one property–structure relationship and distinguishes light emission from point defects versus nanoinclusions.